Global Longitudinal Strain Is a Superior Predictor of All-Cause Mortality in Heart Failure With Reduced Ejection Fraction - Sengeløv, Morten; Jørgensen, Peter Godsk; Jensen, Jan Skov; Bruun, Niels Eske; Olsen, Flemming Javier; Fritz-Hansen, Thomas; Nochioka, Kotaro; Biering-Sørensen, Tor (JACC. Cardiovascular imaging, 2015)
The purpose of this study was to investigate the prognostic value of global longitudinal strain (GLS) in heart failure with reduced ejection fraction (HFrEF) patients in relation to all-cause mortality. Measurement of myocardial deformation by 2-dimensional speckle tracking echocardiography, specifically GLS, may be superior to conventional echocardiographic parameters, including left ventricular ejection fraction, in predicting all-cause mortality in HFrEF patients. Transthoracic echocardiographic examinations were retrieved for 1,065 HFrEF patients admitted to a heart failure clinic. The echocardiographic images were analyzed, and conventional and novel echocardiographic parameters were obtained. Many of the conventional echocardiographic parameters proved to be predictors of mortality. However, GLS remained an independent predictor of mortality in the multivariable model after adjusting for age, sex, body mass index, total cholesterol, mean arterial pressure, heart rate, ischemic cardiomyopathy, percutaneous transluminal coronary angioplasty, coronary artery bypass graft surgery, noninsulin dependent diabetes mellitus, and conventional echocardiographic parameters (hazard ratio [HR]: 1.15; 95% confidence interval [CI]: 1.04 to 1.27; p = 0.008, per 1% decrease). No other echocardiographic parameter remained an independent predictor after adjusting for these variables. Furthermore, GLS had the highest C-statistics of all the echocardiographic parameters and added incremental prognostic value with a significant increase in the net reclassification improvement (p = 0.009). Atrial fibrillation (AF) modified the relationship between GLS and mortality (p value for interaction = 0.036); HR: 1.08 (95% CI: 0.97 to 1.19), p = 0.150 and HR: 1.22 (95% CI: 1.15 to 1.29), p < 0.001, per 1% decrease in GLS for patients with and without AF, respectively. Sex also modified the relationship between GLS and mortality (p value for interaction = 0.047); HR: 1.23 (95% CI: 1.16 to 1.30), p < 0.001 and HR: 1.09 (95% CI: 0.99 to 1.20), p = 0.083, per 1% decrease in GLS for men and women, respectively. GLS is an independent predictor of all-cause mortality in HFrEF patients, especially in male patients without AF. Furthermore, GLS was a superior prognosticator compared with all other echocardiographic parameters.